Phenotypic Plasticity, Developmental Instability, and Robustness: The Concepts and How They Are Connected - Klingenberg, Christian Peter (Frontiers in Ecology and Evolution, 2019)
Developmental systems integrate inputs of variation from different origins into the observable variation of the resulting phenotype. Different components of phenotypic variation can be distinguished that correspond to those inputs, but the response of the system to each input factor can be modulated by other factors, so that there are interactions among the factors. This study uses a simplified developmental model of a trait to illustrate these interactions for genetic variation, phenotypic plasticity in response to temperature variation, and random developmental noise. The simulations show extensive interactions among the input factors, which can be explained by the nonlinear nature of the developmental model. These results are broadly consistent with results from actual biological systems.